Determinan Pengangguran Usia Muda di Sulawesi Utara: Analisis Multilevel pada Tingkat Individu dan Wilayah - Pamelina Alisha Kusumasari; Rini Rahani (Badan Perencanaan Pembangunan, Riset dan Inovasi Daerah Kabupaten Sragen, 2026)
By 2022, North Sulawesi will have the highest youth unemployment rate (15—24 years old) in Eastern Indonesia region (KTI). This is a serious problem given that young people are assets and resources for national development, their potential must be optimally utilized. This study aims to provide an overview of the youth unemployment status, the influence of individual and regional factor, and their trends on the youth unemployment status in North Sulawesi in 2022. The data used comes from the National Labor Force Survey (Sakernas) August 2022, North Sulawesi in Figures 2022 publication Employment Situation of North Sulawesi in 2022, and Gross Regional Domestic Product of North Sulawesi in 2022 publication. It is analyzed using the multilevel logistic regression method with random intercept. The descriptive analysis results indicate that youth unemployment is more prevalent among the youth labor force with unmarried status, at least a high school education, aged 15—19, and female. Furthermore, the inferential analysis demonstrates that marital status, education, age, Gross Regional Domestic Product (GRDP) and realization of local government expenditure affect youth unemployment status significantly.